The development of a test of repeated-sprint ability for elite women's soccer players - Gabbett, T. J. (The Journal of Strength and Conditioning Research, 2010)
The purpose of this study was to develop a game-specific test of repeated-sprint ability for elite women's soccer players. Nineteen elite women's soccer players (mean ± SD; age, 18.1 ± 2.9 y) participated in this study. After familiarization, players completed a repeated-sprint test consisting of 6 × 20-m maximal effort sprints, on a 15-second cycle. At the completion of each sprint, players performed a 10-m deceleration and a 10-m active jog recovery. Ten elite female soccer players performed the test on 2 occasions, 1 week apart, to determine the reliability of the test. In addition, the validity of the repeated-sprint test to discriminate among players of different playing ability was evaluated by testing national (n = 11) and state (n = 8) women's soccer players. Heart rate and blood lactate concentration were recorded to determine the physiological responses to the test. The total sprint time proved to be highly reproducible (intraclass correlation coefficient = 0.91; typical error of measurement = 1.5%). However, the percentage decrement was less reliable (intraclass correlation coefficient = 0.14, typical error of measurement = 19.5%). The repeated-sprint test was valid in discriminating between national- and state-level players, with national players having significantly lower (p < 0.01) total repeated-sprint times than state players (20.9 ± 0.5 s vs. 23.3 ± 0.4 s). The mean (±SD) heart rate and blood lactate concentration were 182 ± 6 beats/min and 9.3± 2.0 mmol/L, respectively. The results of this study demonstrate that the developed repeated-sprint test discriminates players of higher and lesser skill levels and offers a reliable method of assessing repeated-sprint ability in elite women's soccer players when results are expressed as the total sprint time.